2005
DOI: 10.11646/zootaxa.938.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the tachinid parasitoids (Diptera: Tachinidae) of Nearctic Choristoneura species (Lepidoptera: Tortricidae), with keys to adults and puparia

Abstract: The genus Choristoneura (Lepidoptera: Tortricidae) comprises about 16 species in the Nearctic Region and includes several destructive pests of importance to forestry and agriculture. The following 15 species of Tachinidae (Diptera) are recognized as occasional or common parasitoids of Choristoneura species in this region: Actia diffidens Curran, Actia interrupta Curran, Ceromasia auricaudata Townsend, Compsilura concinnata (Meigen), Cyzenis incrassata (Smith), Eumea caesar (Aldrich), Hemisturmia parva (Bigot),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 90 publications
2
27
0
Order By: Relevance
“…3). Second, the most common parasitoid species parasitise all of the budworm species considered here (Huber et al 1996;O'Hara 2005;Bennett 2008;Fernández-Triana and Huber 2010) and several are true generalists, attacking other Lepidoptera hosts. The generalist characteristic of the parasitoid fauna attacking budworms has led to the notion that most parasitoids in budworm outbreaks are opportunistic (Eveleigh et al 2007) and have a limited ability to respond numerically to increases in budworm abundance because of their reliance on alternative hosts to satisfy their seasonal life history requirements (Miller 1963;Blais 1965b;Sanders 1991).…”
Section: Top-down: the Influence Of Natural Enemiesmentioning
confidence: 99%
“…3). Second, the most common parasitoid species parasitise all of the budworm species considered here (Huber et al 1996;O'Hara 2005;Bennett 2008;Fernández-Triana and Huber 2010) and several are true generalists, attacking other Lepidoptera hosts. The generalist characteristic of the parasitoid fauna attacking budworms has led to the notion that most parasitoids in budworm outbreaks are opportunistic (Eveleigh et al 2007) and have a limited ability to respond numerically to increases in budworm abundance because of their reliance on alternative hosts to satisfy their seasonal life history requirements (Miller 1963;Blais 1965b;Sanders 1991).…”
Section: Top-down: the Influence Of Natural Enemiesmentioning
confidence: 99%
“…This study showed that prediction of oviparous attack biology of female N. pyste based on congeneric species was correct (O'Hara 2005). Attachment of unembryonated eggs to host cuticle in the manner of the Winthemiini has long been considered to be an ancestral trait in the Tachinidae (Herting 1960(Herting ,1984Wood 1987).…”
Section: Discussionmentioning
confidence: 81%
“…However, attack behavior and biology has not been described for their Nearctic counterparts N. erecta and N. pyste (O'Hara 2005). In this article, aspects of the reproductive biology of N. erecta and N. pyste that were acquired through the rearing of these species in the laboratory are described.…”
mentioning
confidence: 99%
See 2 more Smart Citations